Peculiarities of photoluminescence spectra behavior in SiC crystals and films during phase transformations - Vlaskina, S.I.; Mishinova, G.N.; Vlaskin, V.I.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Peculiarities of photoluminescence spectra behavior in SiC crystals and thin films with in-grown defects during phase transformations have been studied. On the deep-level(DL)-spectra, as an example, their characteristics and behavior were investigated. It has been shown that all DL spectra have the same logic of construction and demonstrate identical behavior of the thin structure elements.